The Influence of The Quizizz Paper Mode Application on Mathematics Subjects on The Learning Outcomes of Class VI students of SDIT Wihdatul Ummah Takalar - Fatwa, Inayanti; Harjuna, Hariani (PT ARRUS Intelektual Indonesia, 2025)
This study examines how the influence of the quizizz paper mode application on the learning outcomes of elementary school students. This study uses a quantitative research type with an experimental method. The form of research pre-experimental with one-group pretest-posttest design. The population in this study were students of SDIT Wihdatul Ummah Takalar with a sample of 26 female VIB class students. The results of the study showed that the average pretest score was 53.19 and the average posttest score was 82.54, with normally distributed data based on the results of the normality test. The calculation of the hypothesis test obtained a sig (2-tailed) result of 0.000 < 0.05 which indicates that there is an effect of the quizizz paper mode application on mathematics subjects on the learning outcomes of class VI grade students of SDIT Wihdatul Ummah Takalar. Based on the results of the N-Gain test, the average value of increasing learning outcomes is 61.82% which is included in the effective category, indicating that the quizizz paper mode application effectively improves student learning outcomes.